E-prescribing implementation in paediatrics: lessons learned. Issue 6 (9th May 2013) - Benn, C; Bates, I; Akram, A; Shafique, J
Abstract : Implementing electronic prescribing (ePrescribing) in paediatrics is complex and systems may be sub-optimally designed to improve safety. Paediatric prescribing rules and clinical decision support (CDS) are required; Pharmacist involvement in developing CDS may be a significant resource demand. 1 Aims: Identify experiences of pharmacists implementing ePrescribing for paediatric units in NHS hospitals. Compare and contrast with expectations of pharmacists, highlighting similarities in actual and perceived barriers. Recommend evidence-based ways of addressing ePrescribing implementation, with specific reference to paediatrics. Method: Semi-structured, standardised telephone interviews were conducted with 13 pharmacists across GB with responsibilities for implementing ePrescribing; five were 'post implementation', others were about to be, or were involved in a local implementation project (8). The interviews explored themes of roles, expectations, barriers, resources and support. Analysis was conducted using a thematic matrix approach 2 and development of a coding frame. An external analyst reviewed the coding for credibility. Results: Pharmacists involved in an ePrescribing projects described significant impacts on their role and resources in meeting challenges with functionality to manage paediatric requirements in systems designed for adults. Respondents 'post implementation' suggested early identification of an experienced 'risk aware' pharmacist; realistic strategies should be developed to address safety in paediatric dosing by separating paediatric prescribing guidance and dose rounding. Respondents suggested that paediatric formularies and order sets need identifying: some had included all medicines but complex systems may lead to selection errors; others had simplified and only included the most common drugs used in paediatrics. Many had implemented systems without specific paediatric functions for example, dose checking and recommended simple prescribing screens with minimal options. The 'Early planners' had a definite focus on system technicalities and had high expectations for the system. In contrast, experienced respondents had a greater relative focus on engagement and vision and found implementation of ePrescribing in paediatrics has similarities with adult areas. They reported training as a significant planning and resource issue. Our results suggest that early engagement with others who had experience of systems is clearly important. Networking and sharing of best practice seems to be a concern for the respondents interviewed. Conclusions: Lessons can be learnt from those who have implemented ePrescribing. National recommendations suggest that paediatric ePrescribing system implementation should be a later project for Trusts; however, those who have implemented these systems or are in the process of doing so, advise that paediatrics should be prioritised from the start of the process. Pharmacists involved in implementation need support, and desire networking via existing groups such as Neonatal and Paediatric Pharmacists Group (NPPG) or Royal Pharmaceutical Society (RPS). Managers should be aware of resources for clinical support for paediatric ePrescribing. Issues of engagement, strategy, vision, teamwork and training need to be identified earlier in project designs.